A invisibilidade dos povos indigenas citadinos: o caso de Altamira no advento da UHE Belo Monte - TELES, Arivalto Santos (2023)
In this work, the components of the drama experienced by the city's indigenous residents in the City of Altamira - PA in the process of construction of the UHE Belo Monte are discussed. In addition to the bibliographic review work, two field interviews were carried out. The general objective is to analyze in what way and how the Belo Monte hydroelectric plant affected and affected the lives of the indigenous people in Altamira.